Mn3O4 nanoparticles@reduced graphene oxide composite: An efficient electrocatalyst for artificial N2 fixation to NH3 at ambient conditions - Huang, Hong; Gong, Feng; Wang, Yuan; Wang, Huanbo; Wu, Xiufeng; Lu, Wenbo; Zhao, Runbo; Chen, Hongyu; Shi, Xifeng; Asiri, Abdullah M.; Li, Tingshuai; Liu, Qian; et al. (Nano research, 2019)
Currently, industrial-scale NH 3 production almost relies on energy-intensive Haber-Bosch process from atmospheric N 2 with large amount of CO 2 emission, while low-cost and high-efficient catalysts are demanded for the N 2 reduction reaction (NRR). In this study, Mn 3 O 4 nanoparticles@reduced graphene oxide (Mn 3 O 4 @rGO) composite is reported as an efficient NRR electrocatalyst with excellent selectivity for NH 3 formation. In 0.1 M Na 2 SO 4 solution, such catalyst obtains a NH 3 yield of 17.4 μg·h −1 ·mg −1 cat . and a Faradaic efficiency of 3.52% at −0.85 V vs. reversible hydrogen electrode. Notably, it also shows high electrochemical stability during electrolysis process. Density functional theory (DFT) calculations also demonstrate that the (112) planes of Mn 3 O 4 possess superior NRR activity.